Chasing a Little-Known Fairy Bee (Perdita meconis) in a Dynamic Desert Landscape - Sarit Chanprame; Colleen Meidt; Terry Griswold; Joseph S. Wilson; Kelsey K. Graham (Insects)
It is widely understood that bees play an important role in many different ecosystems, due to the services they provide as pollinators [...]